A Study of Reflective Journals Written by Student-teachers during School Internship Programme - Sehrawat, Meena; Roy, M.M. (JOURNAL OF INDIAN EDUCATION, 2020)
The main purpose of reflection is to make sure that all students learn more effectively and meaningfully. Reflective practice makes you accountable for yourself and for the progress of your students. By self-assessing strengths and weaknesses in your teaching, you can explore the factors that hamper your teaching-learning process and the areas where development might be needed. In SCERT, Delhi D.El.Ed course student-teachers write their reflective journal for 40 days per year during the school internship programme as a part of practicum. The present study focuses on the reflective thinking, which studentteachers do before, during and after the teaching-learning process along with the self-assessment to improve their practices. All 26 student-teachers of two investigators were oriented about writing reflective journals but only four student-teachers were randomly selected as sample. Content analysis of the reflective journals written by the student-teachers showed various reflective aspects such as student-teacher relationship, teaching-learning process, selfassessment, teachers’ responsibility— codes and conducts and classroom environment.